Perbedaan Kemampuan Menulis Teks Prosedur Sebelum dan Sesudah Menggunakan Media Google Classroom Siswa Kelas XI SMA Negeri 6 Kota Bengkulu - Jon Kenedi; Gumono Gumono; Suryadi Suryadi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
Students' writing procedural text skills are still low because students do not understand the steps of writing procedural text and its language characteristics. The implementation of Google Classroom is predicted to significantly affect the ability to write procedure text. For this reason, the purpose of this study was to determine the ability to write procedure texts before using Google Classroom media, to determine the ability to write procedure texts after using Google Classroom media, and to determine the differences in the ability to write procedure texts before and after using Google Classroom media for class XI students of SMA Negeri 6 Kota Bengkulu. The research method used is a quasi-experimental method, namely one group pre-test-post test. The research was conducted at SMA Negeri 6 Kota Bengkulu from October to December 2020. The samples taken were 35 students of class XI IPS A for the academic year 2020/2021. Data were analyzed using hypothesis testing (t-test). The results showed that the ability to write procedure text before using Google Classroom was 25.14 in the high category and after using Google Classroom was 35.37 in the very high category. Based on the results of the t-test analysis, it states that there is a difference in the ability to write procedure texts before and after using Google Classroom media for class XI IPS students of SMA Negeri 6 Kota Bengkulu, seen the value obtained is significant (2-tailed) which is 0.00 and the t-count value is seen. smaller that is -20,858 than the t table value of -2.03.